Tracking adaptation across scales in Africa’s agriculture sector - Nowak, Andreea C.; Njuguna, Lucy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Presentation at the Adaptation Futures Conference (Montreal, 2-10 October 2023), Session "What do we know about effectiveness of adaptation in reducing climate risks? A review of methodologies and evidence on adaptations in the agri-food systems"